Investigation of extremely low-frequency magnetic field bioeffect at cellular level concerning ICNIRP guidelines and exposure limits - Bajtoš, Marek; Radil, R; Hargasova, Klaudia; Judáková, Zuzana; Čarnecká, Lucia; Janoušek, Ladislav (Lékař a technika, 2021)
The article deals with the possible influence of an extremely low-frequency magnetic field on cellular structures. The work is carried out to verify the change of growth dynamics of exposed samples by application of a time-varying magnetic field, with a specified action value of magnetic flux density, valid in the European Union. The frequency of applied field was preliminarily confirmed as biologically active, under conditions for Ion Parametric Resonance theory, in experimental work focused on targeting Ca2+ ions bound in specific positions on cellular membranes of eukaryotic cells. In thirty experiments, the authors use the dynamics of growth over a time horizon of eight hours to elucidate the effect of the field on the proliferation activity of the cells. Since living beings are exposed to similar electromagnetic fields daily, the presented article shed some light on whether, or not the irradiation has brought a statistically significant effect under conditions specified in ICNIRP guidelines and recommendations.
Keywords: radiační expozice; Radiation Exposure; magnetické pole; elektromagnetická pole; Saccharomyces cerevisiae; biomedicínské technologie; biomedicínský výzkum; vystavení vlivu životního prostředí; Magnetic Fields; Electromagnetic Fields; Environmental Exposure; Biomedical Research; Biomedical Technology; Yeasts; kvasinky